Exploring the influence of digital entrepreneurship on SME digitalization and management. Issue 3 (2nd September 2021) - Franco, Mário; Godinho, Luis; Rodrigues, Margarida
ABSTRACT: Guided by Technology Acceptance Model (TAM), this study aims to examine the influence of digital entrepreneurship on the digitalization and management of small and medium-sized enterprises (SME), as well as contributing to developing this topic which is so far little developed in the scientific world. To this end, data were collected from 71 questionnaires obtained from a sample of SME managers in an inland region of Portugal. This quantitative study resulted in combining the advantages of digital entrepreneurship in 3 factors: efficiency, customer relations and collaborator behaviour. The research hypotheses, proposing that digital entrepreneurship has a positive influence on SME digitalization and management, were supported, i.e. the results show that customer relations and collaborator behaviour are of crucial importance in SME digitalization and management, particularly in those implementing digital entrepreneurship. This study contributes to showing the importance of digital entrepreneurship in SME management and its importance for the future success of this type of firm.